Evaluating a Regional Yield Potential System using the CATWOE Analysis and UCD Approach - Erly Krisnanik; Anita Muliawati; Bambang Tri Wahyono; Kraugusteeliana; Tri Rahayu (International Journal of Informatics and Computation, 2025)
This study evaluates the effectiveness of the User-Centered Design (UCD) and CATWOE approaches in developing the SINPOHAD village information system for mapping and managing regional economic potential. The results show that UCD achieves a higher accuracy score (88%) than CATWOE (83.33%), indicating its superior ability to meet user needs in terms of usability, learnability, efficiency, satisfaction, and accessibility. While CATWOE provides a strong systemic foundation for requirement formulation and transformation processes, its limited consideration of user experience and environmental constraints results in lower performance. The integration of both approaches yields a design that is strategically structured and highly responsive to real user conditions. The findings confirm that SINPOHAD improves governance efficiency, accelerates decision-making, and enhances community participation through intuitive interfaces and spatial data mapping. The system offers a replicable model for other villages, supporting digital transformation initiatives and sustainable regional development.